2004
DOI: 10.1128/jvi.78.12.6370-6380.2004
|View full text |Cite
|
Sign up to set email alerts
|

Intramembrane Proteolysis and Endoplasmic Reticulum Retention of Hepatitis C Virus Core Protein

Abstract: Hepatitis C virus (HCV) core protein is suggested to localize to the endoplasmic reticulum (ER) through

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
101
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(110 citation statements)
references
References 55 publications
6
101
1
1
Order By: Relevance
“…As the processing protease, the novel aspartic proteinase SPP has been proposed (20). Important evidence for this finding came from the use of (Z-LL) 2 -ketone and the expression of a dominant-negative mutant of SPP (9). In either case the action of SPP was inhibited.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As the processing protease, the novel aspartic proteinase SPP has been proposed (20). Important evidence for this finding came from the use of (Z-LL) 2 -ketone and the expression of a dominant-negative mutant of SPP (9). In either case the action of SPP was inhibited.…”
Section: Resultsmentioning
confidence: 99%
“…All proposed C termini of HCV core protein locate within the central hydrophobic domain of the signal peptide that conducts the translocation of E1 to the endoplasmic reticulum (4). Evidence for the involvement of the intramembrane proteinase SPP in the processing of HCV core protein came from inhibitor studies using peptidomimetic (carboxybenzoyl-Leu-Leu) 2 -ketone [(Z-LL) 2 -ketone] and overexpression of the SPP D 219 A lossof-function mutant (9,20). Analysis of the SPP cleavage site revealed that helix-breaking or -bending residues are a prerequisite for SPP cleavage to occur.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Evidences have shown that ER stress occurs in nearly all physiologies related to acute and chronic liver disease including alcoholic liver disease, 29,30) nonalcoholic fatty liver disease, 31) viral hepatitis, 32,33) and drug-induced liver injury (DILI). [34][35][36] The ER plays a crucial role in maintaining cellular homeostasis, regulating protein synthesis, Ca 2+ transportation and drug metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…22 Studies by others have demonstrated that the HCV core protein 1 is cleaved by signal peptidases between residues 191 and 192 to generate the retained E1 envelope. 23,24 PHC09 contains 10 amino acids (SAIHIRNASG). The major (8 amino acids) molecular mimicry sequence (IHIRNASG) is located in the retained HCV 1 envelope region, which is likely to retain the epitope specificity.…”
Section: Discussionmentioning
confidence: 99%